STRATEGI STRATEGI PERMAINAN EDUKATIF UNTUK MENSTIMULUS PERKEMBANGAN KOGNITIF ANAK USIA DINI - Nurmiyanti, leni; Fatiya Humaira; Imelda Putri Yuliastuti; Mutia Yusfita Habibah; Putri Rosdiatun Nazah; Rahmillah; Siti Nurhalizah (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2025)
This study aims to analyze educational game development strategies to stimulate early childhood cognitive development. This type of research is bibliographic, the data collected in this study are two types of data, namely primary data and secondary data. Data was obtained from library research. The results of the study obtained that educational games are effective in improving thinking, problem-solving, and creativity in early childhood. Development strategies should pay attention to the characteristics of children, including the suitability of content to the stage of cognitive development, interesting interactive features, and challenges that support critical thinking. With the right strategy, educational games can be an interesting and optimal learning tool for children's cognitive development.